FACTORS THAT INFLUENCE ENTREPRENEURIAL INTEREST OF FEB STUDENTS OF TARUMANAGARA UNIVERSITY - Rodhiah Rodhiah; Randy Soerijadi (JURNAL ILMIAH EDUNOMIKA, 2024)
Entrepreneurship is an important aspect for economic development in a country, because entrepreneurship can maintain economic balance by opening up jobs in a country and can increase people's income. In Law Number 20 of 2008 concerning MSMEs through a conducive business climate and business development. The development of the business climate is carried out by determining various regulations and policies in various aspects of economic life. Therefore, Micro, Small and Medium Enterprises get the maximum opportunity, protection and business support. Business development is carried out by providing mentoring facilities and strengthening assistance to grow and increase competitiveness. The purpose of this study was to find out 1) the effect of entrepreneurship education on the entrepreneurship interest of Tarumanagara University FEB students, 2) the influence of the family environment on the entrepreneurship interest of Tarumanagara University FEB students, 3) the effect of self-concept on the entrepreneurship interest of Tarumanagara University FEB students. The sample selection technique used in this study was non-probability sampling and the sampling technique used was purposive sampling. Data was taken using an online google form questionnaire with a total of 100 respondents. Data processing in this study uses SmartPLS. The sample in this study was FEB students at Tarumanagara University who had taken entrepreneurship courses and were interested in becoming entrepreneurs. The results of this study are 1) Entrepreneurship education has no effect on the entrepreneurship interest of FEB Tatumanagara University students, 2) The family environment has no effect on the entrepreneurship interest of FEB Tarumanagara University students, 3) Self-concept has a positive effect on the entrepreneurship interest of FEB Tarumanagara University students. Keywords: Entrepreneurship Education, Family Environment, Self-Concept, and Entrepreneurial Interest